ADVANCING ANATOMY AND PHYSIOLOGY TEACHING IN THE DIGITAL ERA (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
The digital transformation of education is rapidly reshaping how complex subjects like anatomy and physiology are taught. Recent studies show that the COVID-19 pandemic accelerated adoption of digital methods in anatomy education: educators have extensively used online platforms, 3D visualization tools, and virtual labs, and students have quickly adapted to digital delivery of course material. For example, Xiao and Evans report “a significant increase in the employment of digital technologies” in anatomy teaching and note that students have demonstrated an ability to adapt to online learning. However, fully effective pedagogy requires more than just new tools – it demands rethinking how we engage students. As Wickramasinghe et al. emphasize, “digital anatomy has revolutionized undergraduate anatomy education via 3D reconstruction of the human body”, yet this cannot replace traditional methods entirely. Digital tools should complement, not substitute, cadaveric and hands-on learning: as one review notes, digital methods “cannot replace cadaver-based anatomy teaching” but can offer unique, sustainable learning experiences. In short, the methodology must advance to integrate digital innovation with active, student-centered pedagogy [Xiao & Evans, 2022, p. 1138; Wickramasinghe et al., 2022, p. 25, p. 99]